Behavior comparison between bottlenose dolphin (Tursiops spp.) living in Bali Exotic Marine Park captivity and Lovina Beach, Bali - Wijaya, David Keane; Nuarsa, I Wayan; Indrawan, Gede Surya (Jurnal Biologi Udayana; Vol 28 No 2 (2024): JURNAL BIOLOGI UDAYANA, 2025)
The bottlenose dolphin is a species often used in the entertainment industry worldwide. They are the most commonly encountered type of dolphin in aquariums and water parks, where they are featured in shows. This research aims to determine the behavioural differences of Tursiops spp. living in their natural habitat versus in captivity to improve and enhance the quality of life for these animals in captivity. Data collection for this study involved a direct observation method of dolphins at Bali Exotic Marine Park (BEMP) and Lovina Beach for four weeks at each location, with a descriptive analysis of the findings. The results indicate that bottlenose dolphins ( Tursiops spp.) living in their natural habitat exhibit behaviours typical of wild dolphins and do not show signs of stress, demonstrating well-being with non-repetitive and varied behaviour patterns according to their natural activities. In contrast, bottlenose dolphins ( Tursiops spp.) in captivity display behaviours similar to those in the wild but also exhibit abnormal behaviours, including signs of stress such as the occurrence of Repetitive Abnormal Behaviour three times (0.3%), as well as other repetitive behaviours like surface displays, side breaching, chuffing, and sexual behaviours. These behaviours may be attributed to a lack of social interaction with other dolphins, disturbances from humans, and limitations in the captive environment.